Effectiveness of bundled interventions in reducing surgical site infections in elective caesarean sections and caesarean hysterectomies in a tertiary care centre - Yadav, Gunjan; Yadav, Kalpana; Waddar, Parasuram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Surgical site infections are the most common and easily preventable infections complicating surgeries. CDC recommends certain bundle interventions for the prevention of SSIs. Hence the present study was undertaken to see the effectiveness and feasibility of the bundle interventions in the elective caesarean sections and caesarean hysterectomies. Methods: A total of 600 patients were taken. Bundled interventions were applied in 278 caesarean sections and 26 caesarean hysterectomies. Routine care was implemented in 262 caesarean sections and 34 caesarean hysterectomies. Rate of SSI, risk factors associated and treatment outcomes were studied. Results: 8 out of 304 cases of the bundled intervention group developed SSI, giving a rate of 2.6%. 52 cases out of 296 in the routine care group developed SSI, the SSI rate being 17.5%. Anemia and diabetes were the most common risk factors. Conclusions: Adherence to bundled interventions can significantly and easily reduce the incidence of SSI.